Utilization of biomass-derived activated carbon as catalyst support and bioadsorbent in biodiesel production using waste cooking oil as feedstock - Ahmad Farid, Mohammed Abdillah (2017)
The depletion of non-renewable fossil fuels and the growing environmental awareness, biodiesel is seen as a promising substitute for the conventional diesel. Its eco-friendly properties such as being renewable, biodegradable and less carbon emission have brought new hope for a greener future. Presently, waste cooking oil and oil palm empty fruit bunch were extensively used as the raw materials for a low-cost feedstock and catalyst for biodiesel production. Apart from its economic objective, exploitation of these abundant waste sources for biodiesel production is a step ahead in saving the environment from pollution, as it is typically being disposed indiscriminately. In this study, improved production of biodiesel from waste cooking oil was achieved by using a newly developed potassium phosphate tri-basic supported activated carbon catalyst. In order to produce high surface area activated carbon, press-shredded oil palm empty fruit bunch was subjected to carbonization at 700ᴼC for 2 h followed by activation with potassium hydroxide at 700ᴼC for 2 h. To produce the catalyst, calcination was performed at different potassium phosphate tri-basic impregnation concentrations (1:0.25 to 1:1 activated carbon to potassium phosphate tri-basic weight ratio) and temperatures (400ᴼC to 700ᴼC). Prior to transesterification, waste cooking oil was analysed for its physicochemical properties and pre-treated to remove moisture and residues. Under the optimum condition of 5 wt% catalyst loading, 12:1 methanol to oil molar ratio at 60ᴼC for 4 h, 98% of biodiesel yield was achieved, which surpassed the European Biodiesel Standard (EN 14214). The catalyst was reusable for 5 successive reaction cycles, achieving almost 80% of biodiesel yield.In addition, the activated carbon produced from the press-shredded oil palm empty fruit bunch was also utilized as bioadsorbent to remove impurities from the crude biodiesel. The purification process was performed using different adsorbent loadings (1 to 5 wt%) under continuous stirring condition at 500 rpm for 1 h. Approximately 89.71% of methanol, 81.74% of water, 36.67% of FFA and 98.61% of potassium (K) were successfully removed after purification at 5 wt% of bioadsorbent loading, which met the European Biodiesel Standards (EN 14214). In comparison to other commercial adsorbents and conventional water washing method, purification using the biomassderived bioadsorbent resulted in better removal of methanol, water and triglyceride impurities with only a small loss of biodiesel yield.